Válság és prosperitás a munkaerőpiacon. A munkanélküliség regionális sajátosságai Magyarországon 1990–1996 között - Fazekas, Károly (Tér és Társadalom, 1997)
The transition period in Hungary was characterised by increasing and long-standing mass-unemployment. The process resulted in wide and lasting gaps between regions. Industrial employment seems to have declining significance in regional differences but economic development rested on entrepreneurial activity is increasingly important from this point of view. For this reason, diffusion of prosperity has a major role in diminishing territorial disparities on the labour market. Results of the regression analysis implied that the skills of labour have significant impact on regional development through the spatial diffusion and density on enterprises. In this indirect way, quality of skills effects economic development. The analysis also suggested the spatial distribution of foreign investments and the level labour skills to be also related: greater density of foreign capital coincides with higher level of education. Spatial diffusion of entrepreneurial activities is also dependent on geographical situation of distinct regions. Distance form the main European innovation centres and the skill of the labour in the region expounded regional disparities in the density of enterprises adequately. For this reason, regional policy should concentrate on the development of transportation networks and the education system furthermore, specific programmes to improve the status of gypsies on the labour market.